Subject-activity model in forming officer’s leadership competence in the Academy of Ground Forces of Ukraine - BOYKO, Oleg (Journal of Education, Technology and Computer Science, 2013)
Thus, we defined the essence of leadership competency of the future officer and exposed parts of didactic model of its formation, based on the concept of subject-activity training of military specialists and implemented in the educational process of the Academy of Armed Forces named after hetman Petro Sagaydachnyi (see scheme 2). Prospects for further researches can be: justification and development of methods of leadership competence formation of officers in schools and experimental verification of its effectiveness.